The effect of a water games educational program using (Floating Water Short) in learning freestyle swimming for beginners (Journal of Humanities and Social Sciences Research, 2023)
The study aimed to prepare an educational program for water games using (Floating Water Short) and to know the extent of its impact on the development and learning of free swimming for beginners. Choosing the research sample by random method (lottery), represented by: participants (beginners)In the educational summer courses and ages (10-12) years in the Spanish swimming pool in Babylon, and the number of the research sample (24) beginners was divided into two groups, so the number of the experimental group (12) beginners and the same number of the control group (12) beginners, and after completing the testing process And the measurement of the research variables for two tests, pre and post, and after applying the research experiment, the results were reached as follows:- The educational program had a positive effect by using the educational method (float shorts) in learning the float skill through the superiority of the experimental group over the control group in the intermediate test results (floating).Then the researchers recommended:- Using the educational program to learn free swimming skills and for other age groups.- The use of the educational program with water games with beginners has a great impact on the speed of adaptation to the water environment.